Losing Your Gut Feelings. Intuition in Depression - Remmers, Carina; Michalak, Johannes (Frontiers in Psychology, 2016)
Whereas in basic research, intuition has become a topic of great interest, clinical research and depression research in specific have not applied to the topic of intuition, yet. This is astonishing because a well-known phenomenon during depression is that patients have difficulties to judge and decide. In contrast to healthy individuals who take most daily-life decisions intuitively (Kahneman, 2011), depressed individuals seem to have difficulties to come to fast and adaptive decisions. The current article pursues three goals. First, our aim is to establish the hypothesis that intuition is impaired in depression against the background of influential theoretical accounts as well as empirical evidence from basic and clinical research. The second aim of the current paper is to provide explanations for recent findings on the depression-intuition interplay and to present directions for future research that may help to broaden our understanding of decision difficulties in depression. Third, we seek to propose ideas on how therapeutic interventions can support depressed individuals in taking better decisions. Even though our knowledge regarding this topic is still limited, we will tentatively launch the idea that an important first step may be to enhance patients’ access to intuitions. Overall, this paper seeks to introduce the topic of intuition to clinical research on depression and to hereby set the stage for upcoming theory and practice.